Hydrogen Sulfide Promotes Thyroid Hormone Synthesis and Secretion by Upregulating Sirtuin-1 - Xue Zhao; Yedi Cao; Hongfang Jin; Xiuli Wang; Lanbo Zhang; Yang Zhang; Yang Yu; Youyuan Huang; Ying Gao; Junqing Zhang (Frontiers Media S.A., 2022)
Objective: One mechanism of hypothyroidism involves the disruption of thyroid hormone synthesis and secretion by thyrocytes. Hydrogen sulfide (H2S), as a gas signaling molecule, participates in many physiopathologic processes by upregulating sirtuin-1 (SIRT1). The aim of the current study was to explore whether H2S promotes the synthesis and secretion of thyroid hormones by upregulating SIRT1.Methods: Real-time PCR and immunohistochemistry were used to detect the mRNA and protein expression of H2S-generating enzymes in normal human thyroid tissues. Serum H2S concentrations from hypothyroid patients (n = 32) and euthyroid participants (n = 41) were detected by H2S-selective sensors. Thirty-one Sprague-Dawley rats were divided into control group (n = 10), hypothyroid group (induced by MMI, n = 10) and hypothyroid + NaHS group (n = 11), and the FT4, TT4 and TSH levels were assayed. Human primary thyrocytes were incubated with H2S donor sodium hydrosulfide (NaHS) or NaHS plus SIRT1 inhibitor (EX527) in vitro. Thyroid hormone synthesis- and secretion-related proteins [thyroid peroxidase (TPO), sodium iodide transporter (NIS), Pendrin, monocarboxylic acid transporter 8 (MCT8)] were analyzed by real-time PCR and Western blot.Results: H2S levels in serum from hypothyroid patients were decreased compared to those from euthyroid participants (p < .05), and serum H2S levels were positively correlated with FT3, FT4, TT3, and TT4 levels in all subjects (all p < .0001). In vivo, NaHS promoted thyroid function in hypothyroid rats (p < .05). In vitro, H2S was detected in supernatant, and CBS mRNA was higher than CSE and 3-MPST in human primary thyrocytes (p < .05). The protein levels of TPO, NIS, Pendrin and MCT8 were upregulated in a concentration-dependent manner for NaHS in thyrocytes. After blocking SIRT1 with EX527, we found that the increasing levels of TPO, NIS, Pendrin, and MCT8 and TPO activity were downregulated in thyrocytes incubated with NaHS, and FT4 levels in the cell supernatant were also decreased significantly (all p < .05).Conclusion: H2S is mainly generated in thyrocytes by CBS. Serum H2S levels are decreased with hypothyroidism. H2S promotes the synthesis and secretion of thyroid hormones and the expression of related molecules by upregulating SIRT1.